계량서지적 분석을 활용한 핵심 담수화 기술의 연구 동향 - 이경훈; 김혜원; 부찬희; 백영빈; 곽노균; 김춘수; 정성필 (대한상하수도학회, 2021)
The global water shortage is getting more attention by global climate change. And water demand rapidly increases due to industrialization and population growth. Desalination technology is being expected as an alternative water supply method. Desalination technology requires low energy or maintenance costs, making it a competible next generation technology, with examples such as forward osmosis (FO), membrane distillation (MD), capacitive deionization (CDI), and electrodialysis (ED) to compete with reverse osmosis (RO). In order to identify recent research trends in desalination technologies (FO, MD, RO, CDI, and ED) between 2000-2020, a bibliometric analysis was conducted in the current study. The number of published papers in desalination technology have increased in Desalination and Journal of Membrane Science mainly. Moreover, it was found that FO, MD, RO, CDI, and ED technologies have been applied in various research areas including electrochemical, food processing and carbon-based material synthesis. Recent research topics according to the desalination technologies were also identified.